Method for preparing environment-friendly plasticizer material hydrogenation catalyst from diisononyl phthalate

By combining the magnesium aluminum silicate support and Os-Zr bimetallic active components, the problems of harsh reaction conditions and insufficient catalyst stability in the prior art are solved, and high efficiency under low pressure and low hydrogen ester ratio conditions are achieved DINCH hydrogenation reaction.

CN119488902AActive Publication Date: 2025-02-21CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202311046158.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-18
Publication Date
2025-02-21
Estimated Expiration
2043-08-18

AI Technical Summary

Technical Problem

In the preparation of cyclohexane 1,2-dicarboxylate, the reaction conditions are harsh, ultra-high pressure is required, and the stability and selectivity of the catalyst are insufficient, which limits the process of domestic chemical industry.

Method used

Magnesium aluminum silicate is used as the base carrier to form a multi-dimensional layered carrier structure through neutralization reaction and dilute hydrochloric acid modification. At low temperature, the Os-Zr bimetallic active component is highly combined with the carrier to form a stable structure. .

Benefits of technology

In the continuous drip bed reactor, the catalyst can run for a long time, maintain good selectivity, activity and stability, adapt to the reaction conditions of lower hydrogen ester ratio, and improve the efficiency of DINCH hydrogenation reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119488902A_ABST
    Figure CN119488902A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysis, and particularly relates to a preparation method of an environment-friendly plasticizer material hydrogenation catalyst based on a diisononyl phthalate source. The preparation method comprises the following steps: preparing a modified calcium-aluminum composite carrier by taking aluminum-magnesium silicate as a substrate, and simultaneously loading active components Os and Zr onto the carrier through an equivalent-volume impregnation method at a low temperature to obtain a catalyst finished product. The catalyst for hydrogenation of diisononyl phthalate prepared by the invention can still keep good selectivity, activity and stability after long-time operation in a continuous trickle bed reactor under the condition of lower hydrogen-ester ratio; the active component Zr and the precious metal active component Os are competitively adsorbed on the carrier to form a stable structure, the dosage of the precious metal Os is small, the loss rate is low, and the stability of the catalyst is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysis, and in particular relates to a method for preparing a catalyst based on hydrogenation of diisononyl phthalate to prepare cyclohexane 1,2-dicarboxylate. Background Art

[0002] In recent years, as people's awareness of environmental protection has increased and their requirements for healthy living have increased, low-toxic phthalate plasticizers (such as DINP) used in food packaging, pharmaceutical industry, etc. have become increasingly rejected, and are being replaced by non-toxic substitutes (such as DINCH) with strong comprehensive performance. In addition, my country's plastics industry is developing rapidly, and the plasticizer industry is growing at a rate of more than 10% per year. The annual production capacity of phthalate plasticizers (such as DINP) has exceeded 3 million tons, and there is overcapacity. One way to solve these two problems is to convert the overcapacity DINP into non-toxic DINCH by hydrogenation.

[0003] BASF of Germany uses patent US6284917B1 to prepare Ru / Al 2 O 3 The catalyst has achieved the industrialization of diisononyl phthalate hydrogenation at 20MPa, but the reaction conditions are harsh and need to be carried out under ultra-high pressure, which places high demands on the reactor material and safety management in the production process.

[0004] U.S. Patent US7361714B2 introduces a supported Ru, Pt, Rh, Co or Ni catalyst. When the mass fraction of Ru is 1%, the yield of DINCH can reach 99.5% at a temperature of 120°C and a pressure of 20 MPa for 2 hours. The reaction pressure is high and there is no data for long-term operation, so the stability of the catalyst is unknown.

[0005] Chinese patent CN115709064A introduces an eggshell-type catalyst for selective hydrogenation to prepare DINCH, whose active components are composed of precious metals and lanthanide metals. In a fixed bed microreactor, under the conditions of temperature 150°C, pressure 4.0MPa, and hydrogen-ester ratio of 600:1, its raw material conversion rate is 86~100%, and the product selectivity is 80~99.61%. The reaction pressure is low but the hydrogen-ester ratio is too high, and the reaction volume is small (only 1g). If the internal diffusion effect cannot be eliminated, the amplification effect cannot be predicted.

[0006] Chinese patent CN111036279A introduces a Ru / HY zeolite-SiO 2Catalyst, after loading 1.1g of catalyst in a 100ml intermittent reactor at a temperature of 100℃ and a pressure of 1~2MPa and reacting for 4h, the DINP conversion rate can reach 99.9% and the DINCH yield can reach 99.9%. Although the reaction pressure dropped significantly, the reaction volume was small and the reaction was carried out in a non-continuous state. Only the data after 4h of reaction were tested, and the stability is unknown.

[0007] At present, the existing phthalate hydrogenation technology still has problems such as harsh reaction conditions, small reaction scale, short reaction time, inability to achieve continuous process, and excessive hydrogen-ester ratio, which hinders the domestic industrial process of phthalate hydrogenation to produce cyclohexane dicarboxylate.

[0008] Therefore, the technicians in this field intend to prepare a catalyst that can adapt to a lower hydrogen-ester ratio and has excellent activity and stability in a continuous reaction process under relatively mild reaction conditions. However, under this condition, since the reaction pressure is relatively low compared to traditional mature reaction processes abroad, in order to ensure that the hydrogen-ester ratio continuously passing through the bed is still low, the catalyst needs to have good selectivity and stability, which requires the development of a catalyst with a strong bond between the active component and the carrier and suitable parameters such as porosity, so as to enhance the contact and mass transfer of the gas-liquid two phases on the catalyst surface, thereby achieving the purpose of obtaining good product selectivity and raw material conversion rate even if the pressure and hydrogen-ester ratio are low and the catalyst bed is continuously passed for a long time. Summary of the invention

[0009] The purpose of the present invention is to provide a method for preparing an environmentally friendly plasticizer material hydrogenation catalyst based on diisononyl phthalate, which solves the problems of poor catalyst activity, selectivity and stability when the catalyst runs for a long time under low pressure and hydrogen-ester ratio in a continuous trickle bed reactor.

[0010] The main features of the present invention are: 1) Magnesium aluminum silicate is used as a substrate, which is both a dispersant and a structure modifier. It plays an auxiliary role when the alkaline solution and the aluminum nitrate solution are neutralized in parallel to obtain a primary modified sodium aluminum or potassium aluminum or sodium potassium aluminum suspension. The suspension is then mixed with calcium hydroxide and modulated with dilute hydrochloric acid to form a secondary modified calcium sodium aluminum or calcium potassium aluminum or calcium sodium potassium aluminum carrier precursor, which is then filtered, dried, calcined, etc. to form a multi-dimensional layered carrier architecture composed of crystal forms such as Na-Al-O-Ca, Ca-O-Al-K, Al-O-Na, Al-OO-Al, Al-OO-Ca, Ca-O-Al-KO-Mg, Ca-O-Al-Na-Mg-O-Si, Ca-O-Al-K-Mg-O-Si, etc. Such a carrier has a high degree of bonding with the active components Os and Zr and suitable pores, so that the activity and stability of the catalyst can also be improved; 2) Os-Zr bimetallic is used as the active component. The carrier is impregnated in a mixed salt solution of Os and Zr by an equal volume impregnation method under low temperature conditions, so that the bimetallic active components compete for adsorption on the carrier. Subsequently, they are highly bonded to the carrier through calcination, so that the catalyst can maintain good DINCH hydrogenation selectivity after long-term use.

[0011] The invention provides a preparation method of an environmentally friendly plasticizer material hydrogenation catalyst sourced from diisononyl phthalate, characterized in that a magnesium aluminum silicate dispersion is used as a base liquid, an alkali solution and an aluminum nitrate solution are added thereto in parallel for neutralization reaction to obtain a primary modified sodium aluminum or potassium aluminum or sodium potassium aluminum suspension, the suspension is mixed with calcium hydroxide and modulated with dilute hydrochloric acid to form a secondary modified calcium sodium aluminum or calcium potassium aluminum or calcium sodium potassium aluminum carrier precursor, which is then filtered, dried and calcined to form a carrier with a multi-dimensional layered structure, the carrier is impregnated in a mixed salt solution of Os and Zr by an equal volume impregnation method at low temperature to obtain a catalyst precursor, and the finished catalyst is obtained by washing, drying and calcining.

[0012] Furthermore, the method for preparing the catalyst of the present invention comprises the following steps: a. Mix aluminum magnesium silicate and water at a mass ratio of 0.2-0.4:100 to prepare an aluminum magnesium silicate dispersion; b. Prepare 0.2~0.4mol / L aluminum nitrate solution rich in metal aluminum ions; prepare 1.25~2.5mol / L alkaline precipitant; c. Add the two solutions obtained in step b to the dispersion obtained in step a in parallel under constant temperature stirring for neutralization and precipitation, and control the end point pH value to be 7.2-8.0 to obtain a primary sodium aluminum or potassium aluminum or sodium potassium aluminum suspension; d. Dissolve calcium hydroxide in water to prepare a 0.125-0.25 mol / L (calculated as metallic calcium) suspension, control the stirring speed to 150-350 rpm, slowly add the suspension obtained in step c, and simultaneously slowly add a dilute hydrochloric acid solution with a volume ratio of 1:10-1:15, control the endpoint pH value to 7.5, and prepare a secondary calcium sodium aluminum or calcium potassium aluminum or calcium sodium potassium aluminum suspension; e. Filter the suspension obtained in step d, dry it for the first time, roast it for the first time, and sieve it to obtain a 5-10 mesh carrier; f. Prepare a mixed aqueous solution of 0.008-0.016 mol / L of osmium rich in active component and 0.04-0.12 mol / L of zirconium rich in active component, control the temperature at 10-20°C, and immerse the carrier obtained in step e in the solution for 1-2 hours by an equal volume impregnation method to obtain a catalyst precursor; then immerse the impregnated catalyst precursor in 5%-8% (by mass) NaBH 4 Immerse in the solution for 1-2 hours, take out, wash with distilled water, dry for the second time, and calcine for the second time to obtain the finished catalyst.

[0013] Preferably, the aluminum nitrate solution in the above steps is a solution prepared by dissolving aluminum nitrate nonahydrate in water, the alkaline precipitant is a solution prepared by dissolving one or both of sodium hydroxide and potassium hydroxide in water, and the Na:K molar ratio when the sodium hydroxide and potassium hydroxide solutions are mixed is 1:1.

[0014] The constant temperature in the above steps is an oil bath with a temperature of 50-70° C. and a stirring speed of 100-300 rpm.

[0015] In the above steps, the addition rate of the aluminum nitrate solution during the parallel flow is 15-30 ml / min, and the addition rate of the alkaline precipitant is 10-20 ml / min.

[0016] The mixed solution of active components osmium and zirconium in the above steps is a mixture of potassium chloroosmate and zirconium nitrate.

[0017] The molar ratio of Al: Ca in the carrier in the above steps is 0.8~1.6:1.

[0018] In the above steps, the first drying temperature is 120-160°C, and the first calcination temperature is 550-650°C.

[0019] In the above steps, the loading amounts of the active components osmium and zirconium are 0.06-0.12% and 0.15-0.45% of the catalyst weight respectively.

[0020] In the above steps, the second drying temperature is 110-130° C., the second calcination temperature is 350-450° C., and the calcination atmosphere is nitrogen.

[0021] The catalyst for hydrogenation of diisononyl phthalate prepared by the present invention can maintain good selectivity, activity and stability when operated for a long time in a continuous trickle bed reactor under the condition of a low hydrogen-ester ratio; the active component Zr competes with the noble metal active component Os for adsorption on the carrier to form a stable structure, the amount of noble metal Os used is small and the loss rate is low, and the catalyst has good stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 It is a microstructure photograph of the carrier in the embodiment of the present invention. Implementation

[0023] The method of the present invention is described in detail below through examples and drawings, but the examples are only used to illustrate the invention and do not constitute a limitation on the scope of the present invention. Example 1

[0024] 1) Mix aluminum magnesium silicate and water at a mass ratio of 0.2:100 to prepare 1L aluminum magnesium silicate dispersion; 2) Take 0.2mol / L aluminum nitrate solution rich in metal aluminum ions and 1L of 1.25mol / L sodium hydroxide solution; 3) Under a 50°C constant temperature oil bath, control the stirring speed to 100rpm, add aluminum nitrate and sodium hydroxide solution to the aluminum magnesium silicate dispersion in parallel for neutralization precipitation, control the addition speed of aluminum nitrate solution to 30ml / min, the addition speed of sodium hydroxide solution to 15ml / min, and the end point pH value to 7.2 to obtain a first-grade sodium aluminum or potassium aluminum or sodium potassium aluminum suspension; 4) Take 0.25mol / L (in terms of metal calcium) hydroxide 1L of calcium chloride suspension was added, the stirring speed was controlled at 350rpm, and the primary sodium aluminum suspension was slowly added, and at the same time, a dilute hydrochloric acid solution with a volume ratio of 1:10 was slowly added, and the end point pH value was controlled to be 7.5 to obtain a secondary calcium sodium aluminum suspension; 5) The secondary calcium sodium aluminum suspension was filtered, dried at 160℃, calcined at 550℃, and sieved to obtain a 5-10 mesh carrier; 6) A mixed aqueous solution of 0.008mol / L of active component osmium and 0.12mol / L of active component zirconium was prepared, the temperature was controlled at 20℃, and the carrier was immersed in it for 2h by an equal volume impregnation method to obtain a catalyst precursor; 7) The impregnated catalyst precursor was placed in 5% (by mass) NaBH 4 After being immersed in the solution for 1 hour, the catalyst was taken out, washed with distilled water, dried at 110°C, and calcined at 350°C under a nitrogen atmosphere to obtain a finished catalyst I rich in 0.06% Os-0.45% Zr active components. Example 2

[0025] 1) Mix aluminum magnesium silicate and water at a mass ratio of 0.4:100 to prepare 1L aluminum magnesium silicate dispersion; 2) Take 1L each of 0.4mol / L aluminum nitrate solution rich in metal aluminum ions and 1.5mol / L potassium hydroxide solution; 3) Under a 70°C constant temperature oil bath, control the stirring speed to 200rpm, add aluminum nitrate and potassium hydroxide solution to the aluminum magnesium silicate dispersion in parallel for neutralization precipitation, control the addition speed of aluminum nitrate solution to 15ml / min, the addition speed of potassium hydroxide solution to 20ml / min, and the end point pH value to 8.0 to obtain a primary potassium aluminum suspension; 4) Take 0.125mol / L (in terms of metallic calcium) calcium hydroxide suspension 5) The secondary calcium potassium aluminum suspension was filtered, dried at 160°C, calcined at 650°C, and sieved to obtain a 5-10 mesh carrier; 6) A mixed aqueous solution of 0.008 mol / L of osmium and 0.04 mol / L of zirconium was prepared, the temperature was controlled at 10°C, and the carrier was immersed in it for 1 hour by an equal volume impregnation method to obtain a catalyst precursor; 7) The impregnated catalyst precursor was placed in 8% (by mass) NaBH 4 After being immersed in the solution for 1 hour, the catalyst was taken out, washed with distilled water, dried at 110°C, and calcined at 450°C under a nitrogen atmosphere to obtain a finished catalyst II rich in 0.06% Os-0.15% Zr active components. Example 3

[0026] 1) Mix aluminum magnesium silicate and water at a mass ratio of 0.3:100 to prepare 1L aluminum magnesium silicate dispersion; 2) Take 0.4mol / L aluminum nitrate solution rich in metal aluminum ions and 1.25mol / L potassium hydroxide solution, each 1L; 3) Under a 60°C constant temperature oil bath, control the stirring speed to 200rpm, add aluminum nitrate and potassium hydroxide solution to the aluminum magnesium silicate dispersion in parallel for neutralization precipitation, control the addition speed of aluminum nitrate solution to 25ml / min, the addition speed of potassium hydroxide solution to 15ml / min, and the end point pH value to 7.8 to obtain a first-grade potassium aluminum suspension; 4) Take 0.179mol / L (in terms of metallic calcium) calcium hydroxide suspension 1.4L, control the stirring speed to 350rpm, slowly add the suspension obtained from the first-level potassium aluminum, and at the same time slowly drop a dilute hydrochloric acid solution with a volume ratio of 1:12, control the endpoint pH value to 7.5, and obtain a second-level calcium potassium aluminum suspension; 5) filter the second-level calcium potassium aluminum suspension, dry it at 140℃, roast it at 600℃, and sieve it to obtain a 5-10 mesh carrier; 6) prepare a mixed aqueous solution of 0.016mol / L rich in active component osmium and 0.04mol / L rich in active component zirconium, control the temperature at 15℃, and immerse the carrier in it for 2h by an equal volume impregnation method to obtain a catalyst precursor; 7) put the impregnated catalyst precursor into 6% (by mass) NaBH 4 After being immersed in the solution for 1 hour, the catalyst was taken out, washed with distilled water, dried at 130°C, and calcined at 400°C under a nitrogen atmosphere to obtain a finished catalyst III rich in 0.12% Os-0.15% Zr active components. Example 4

[0027] 1) Mix aluminum magnesium silicate and water at a mass ratio of 0.25:100 to prepare 1L aluminum magnesium silicate dispersion; 2) Take 0.3mol / L aluminum nitrate solution rich in metal aluminum ions and 1L of 2.0mol / L mixed solution of sodium hydroxide and potassium hydroxide; 3) Under a 70°C constant temperature oil bath, control the stirring speed to 300rpm, add aluminum nitrate, sodium hydroxide and potassium hydroxide mixed solution to the aluminum magnesium silicate dispersion in parallel for neutralization and precipitation, control the addition speed of aluminum nitrate solution to 25ml / min, and the addition speed of sodium hydroxide and potassium hydroxide mixed solution to 10ml / min, and the end point pH value is 7.4 to prepare a primary sodium potassium aluminum suspension; 4) Take 0.2mol / L (calculated as metallic calcium) ) 1.25L of calcium hydroxide suspension, control the stirring speed at 200rpm, slowly add the first-level sodium potassium aluminum suspension, and slowly drop a dilute hydrochloric acid solution with a volume ratio of 1:13, control the end point pH value to 7.5, and obtain a second-level calcium sodium potassium aluminum suspension; 5) Filter the calcium sodium potassium aluminum suspension, dry it at 160℃, roast it at 550℃, and sieve it to obtain a 5-10 mesh carrier; 6) Prepare a mixed aqueous solution of 0.012mol / L rich in active component osmium and 0.08mol / L rich in active component zirconium, control the temperature at 15℃, and immerse the carrier in it for 1.5h by equal volume impregnation method to obtain a catalyst precursor; 7) Put the impregnated catalyst precursor into 7% (by mass) NaBH 4 After being immersed in the solution for 1 hour, the catalyst was taken out, washed with distilled water, dried at 130°C, and calcined at 450°C under a nitrogen atmosphere to obtain a finished catalyst IV rich in 0.09% Os-0.30% Zr active components. Example 5

[0028] 1) Mix aluminum magnesium silicate and water at a mass ratio of 0.2:100 to prepare 1L aluminum magnesium silicate dispersion; 2) Take 1L each of 0.4mol / L aluminum nitrate solution rich in metal aluminum ions and 2.5mol / L sodium hydroxide solution; 3) Under a 50°C constant temperature oil bath, control the stirring speed to 300rpm, add aluminum nitrate and sodium hydroxide solution to the aluminum magnesium silicate dispersion in parallel for neutralization precipitation, control the addition speed of aluminum nitrate solution to 15ml / min, the addition speed of sodium hydroxide solution to 10ml / min, and the end point pH value to 7.2 to obtain a first-grade sodium aluminum suspension; 4) Take 1L of 0.25mol / L (in terms of metal calcium) calcium hydroxide suspension, control The stirring speed is 350rpm, and the primary sodium aluminum suspension is slowly added, and at the same time, a dilute hydrochloric acid solution with a volume ratio of 1:10 is slowly added, and the end point pH value is controlled to be 7.5 to obtain a secondary calcium sodium aluminum suspension; 5) The secondary calcium sodium aluminum or calcium potassium aluminum or calcium sodium potassium aluminum suspension is filtered, dried at 150°C, calcined at 600°C, and sieved to obtain a 5-10 mesh carrier; 6) A mixed aqueous solution of 0.010 mol / L rich in active component osmium and 0.08 mol / L rich in active component zirconium is prepared, the temperature is controlled at 15°C, and the carrier is immersed in it for 1.5 hours by an equal volume impregnation method to obtain a catalyst precursor; 7) The impregnated catalyst precursor is placed in 5% (by mass) NaBH 4 After being immersed in the solution for 1.5 hours, the catalyst was taken out, washed with distilled water, dried at 120°C, and calcined at 450°C under a nitrogen atmosphere to obtain a finished catalyst V rich in 0.075% Os-0.30% Zr active components. Example 6

[0029] 1) Mix aluminum magnesium silicate and water at a mass ratio of 0.35:100 to prepare 1L aluminum magnesium silicate dispersion; 2) Take 0.25mol / L aluminum nitrate solution rich in metal aluminum ions and 1.75mol / L sodium hydroxide and potassium hydroxide mixed solution, each 1L; 3) In a 60°C constant temperature oil bath, control the stirring speed to 150rpm, add aluminum nitrate, sodium hydroxide and potassium hydroxide mixed solution to the aluminum magnesium silicate dispersion in parallel for neutralization and precipitation, control the addition speed of aluminum nitrate solution to 20ml / min, the addition speed of sodium hydroxide and potassium hydroxide mixed solution to 20ml / min, and the end point pH value to 7.2 to prepare a primary sodium potassium aluminum suspension; 4) Take 0.25mol / L (gold) 5) The secondary calcium sodium potassium aluminum suspension was filtered, dried at 130°C, calcined at 600°C, and sieved to obtain a 5-10 mesh carrier; 6) A mixed aqueous solution of 0.016 mol / L of osmium and 0.12 mol / L of zirconium was prepared, the temperature was controlled at 15°C, and the carrier was immersed in it for 2 hours by an equal volume impregnation method to obtain a catalyst precursor; 7) The impregnated catalyst precursor was placed in 5% (by mass) NaBH 4 After being immersed in the solution for 2 hours, the product was taken out, washed with distilled water, dried at 130°C, and calcined at 350°C under a nitrogen atmosphere to obtain a finished catalyst VI rich in 0.12% Os-0.45% Zr active components. Example 7

[0030] 1) Mix aluminum magnesium silicate and water at a mass ratio of 0.2:100 to prepare 1L aluminum magnesium silicate dispersion; 2) Take 1L each of 0.35mol / L aluminum nitrate solution rich in metal aluminum ions and 2.0mol / L potassium hydroxide solution; 3) Under a 50°C constant temperature oil bath, control the stirring speed to 100rpm, add aluminum nitrate and potassium hydroxide solution to the aluminum magnesium silicate dispersion in parallel for neutralization precipitation, control the addition speed of aluminum nitrate solution to 25ml / min, the addition speed of potassium hydroxide solution to 10ml / min, and the end point pH value to 7.6 to obtain a primary potassium aluminum suspension; 4) Take 0.25mol / L (in terms of metallic calcium) calcium hydroxide suspension 1L of liquid, control the stirring speed to 150rpm, slowly add the primary potassium aluminum suspension, and slowly drop a dilute hydrochloric acid solution with a volume ratio of 1:10, control the end point pH value to 7.5, and obtain a secondary calcium potassium aluminum suspension; 5) filter the secondary calcium potassium aluminum suspension, dry it at 120℃, roast it at 580℃, and sieve it to obtain a 5-10 mesh carrier; 6) prepare a mixed aqueous solution of 0.008mol / L rich in active component osmium and 0.04mol / L rich in active component zirconium, control the temperature at 10℃, and immerse the carrier in it for 1h by an equal volume impregnation method to obtain a catalyst precursor; 7) put the impregnated catalyst precursor into 5% (by mass) NaBH 4 After being immersed in the solution for 1 hour, the product was taken out, washed with distilled water, dried at 110°C, and calcined at 450°C under nitrogen atmosphere to obtain the finished catalyst VII rich in 0.06% Os-0.15% Zr active components. Example 8

[0031] 1) Mix aluminum magnesium silicate and water at a mass ratio of 0.3:100 to prepare 1L aluminum magnesium silicate dispersion; 2) Take 1L each of 0.2mol / L aluminum nitrate solution rich in metal aluminum ions and 2.25mol / L sodium hydroxide solution; 3) Under a 50℃ constant temperature oil bath, control the stirring speed to 200rpm, add aluminum nitrate and sodium hydroxide solution to the aluminum magnesium silicate dispersion in parallel for neutralization precipitation, control the addition speed of aluminum nitrate solution to 25ml / min, the addition speed of sodium hydroxide solution to 20ml / min, and the end point pH value to 8.0 to obtain a primary sodium aluminum suspension; 4) Take 0.25mol / L (in terms of metallic calcium) calcium hydroxide suspension 1L, control the stirring speed to 350rpm, slowly add the primary sodium aluminum suspension, and slowly drop a dilute hydrochloric acid solution with a volume ratio of 1:10, control the end point pH value to 7.5, and obtain a secondary calcium sodium aluminum suspension; 5) filter the secondary calcium sodium aluminum suspension, dry it at 120℃, roast it at 550℃, and sieve it to obtain a 5-10 mesh carrier; 6) prepare a mixed aqueous solution of 0.014mol / L rich in active component osmium and 0.04mol / L rich in active component zirconium, control the temperature at 10℃, and immerse the carrier in it for 2h by an equal volume impregnation method to obtain a catalyst precursor; 7) put the impregnated catalyst precursor into 5% (by mass) NaBH 4 After being immersed in the solution for 1 hour, the product was taken out, washed with distilled water, dried at 130°C, and calcined at 400°C in a nitrogen atmosphere to obtain the finished catalyst VIII rich in 0.105% Os-0.15% Zr active components. Example 9

[0032] 1) Mix aluminum magnesium silicate and water at a mass ratio of 0.25:100 to prepare 1L aluminum magnesium silicate dispersion; 2) Take 0.2mol / L aluminum nitrate solution rich in metal aluminum ions and 1L of 2.5mol / L mixed solution of sodium hydroxide and potassium hydroxide; 3) In a 60℃ constant temperature oil bath, control the stirring speed to 200rpm, add aluminum nitrate, sodium hydroxide and potassium hydroxide mixed solution to the aluminum magnesium silicate dispersion in parallel for neutralization and precipitation, control the addition speed of aluminum nitrate solution to 25ml / min, and the addition speed of sodium hydroxide and potassium hydroxide mixed solution to 15ml / min, and the end point pH value is 7.8 to prepare a primary sodium potassium aluminum suspension; 4) Take 0.25mol / L (based on metal calcium ions) 5) The secondary calcium sodium potassium aluminum suspension was filtered, dried at 140°C, calcined at 600°C, and sieved to obtain a 5-10 mesh carrier; 6) A mixed aqueous solution of 0.008 mol / L of osmium and 0.08 mol / L of zirconium was prepared, the temperature was controlled at 15°C, and the carrier was immersed in it for 2 hours by an equal volume impregnation method to obtain a catalyst precursor; 7) The impregnated catalyst precursor was placed in 5% (by mass) NaBH 4 After being immersed in the solution for 2 hours, the catalyst was taken out, washed with distilled water, dried at 130°C, and calcined at 450°C under a nitrogen atmosphere to obtain a finished catalyst product IX rich in 0.06% Os-0.30% Zr active components.

[0033] Comparative Example 1 1) Prepare a 0.018 mol / L solution rich in active component ruthenium; 2) Add 30 g of γ-Al 2 O 3 , 60g calcium hydroxide and 10g potassium hydroxide were added with water and kneaded evenly, and then heat-treated at 500℃ for 2h, and then granulated to obtain 5-10 mesh calcium potassium aluminum carrier, and then immersed an equal volume of it in the above-mentioned Ru salt solution for 2h; 3) The above-mentioned primary catalyst precursor was taken out and dried at 130℃ for 2h and calcined at 450℃ for 2h; 4) 0.08mol / L solution rich in active component zirconium was prepared, and the above-mentioned secondary catalyst precursor was immersed in it again, and then dried at 130℃ for 2h and calcined at 550℃ for 1h, and finally a catalyst product A rich in 0.09%Ru-0.30%Zr active components was obtained.

[0034] Comparative Example 2 1) Prepare a 0.008 mol / L solution rich in the active ingredient osmium; 2) Add 30 g of γ-Al 2 O 3, 60g calcium hydroxide and 10g potassium hydroxide were added with water and kneaded evenly, and then heat-treated at 500℃ for 2h, and then granulated to obtain 5-10 mesh calcium potassium aluminum carrier, and then immersed an equal volume of it in the above-mentioned osmium salt solution for 2h; 3) The above-mentioned primary catalyst precursor was taken out and dried at 130℃ for 2h and calcined at 450℃ for 2h; 4) 0.08mol / L solution rich in active component zirconium was prepared, and the above-mentioned secondary catalyst precursor was immersed in it again, and then dried at 130℃ for 2h and calcined at 550℃ for 1h, and finally a catalyst product B rich in 0.06%Os-0.30%Zr active components was obtained.

[0035] Comparative Example 3 1) Prepare a 0.008 mol / L solution rich in the active ingredient osmium; 2) Add 30 g of γ-Al 2 O 3 50g calcium hydroxide, 10g sodium hydroxide, and 10g potassium hydroxide were kneaded evenly with water, and then heat-treated at 500℃ for 2h to obtain 5-10 mesh calcium sodium potassium aluminum carrier, and then the same volume of the carrier was immersed in the above-mentioned mixed salt solution of osmium and zirconium for 2h; 3) The impregnated catalyst precursor was placed in 5% (by mass) NaBH 4 After being immersed in the solution for 2 hours, the catalyst was taken out, washed with distilled water, dried at 130°C for 2 hours, and calcined at 450°C for 2 hours, and finally a finished catalyst C rich in 0.06% Os active components was obtained.

[0036] Comparative Example 4 1) Prepare 0.3mol / L aluminum nitrate solution rich in metal aluminum ions and 1L of a mixed solution of sodium hydroxide and potassium hydroxide at 2.5mol / L; 2) Add the mixed solution of sodium hydroxide and potassium hydroxide to the aluminum nitrate solution in a 60℃ constant temperature oil bath at a stirring speed of 200rpm to obtain a primary sodium potassium aluminum suspension; 3) Take 1L of a 0.25mol / L (calculated as metallic calcium) calcium hydroxide suspension, control the stirring speed at 250rpm, and slowly add the primary sodium potassium aluminum suspension to obtain a secondary calcium sodium Potassium aluminum suspension; 4) filtering the secondary calcium sodium potassium aluminum suspension, drying at 140°C, calcining at 600°C, and sieving to obtain a 5-10 mesh carrier; 5) preparing a mixed aqueous solution of 0.009 mol / L rich in active component ruthenium and 0.04 mol / L rich in active component zirconium, and immersing the carrier therein for 2 hours using an equal volume impregnation method to obtain a catalyst precursor; 6) taking out, washing once with distilled water, drying at 130°C, and calcining at 450°C to obtain a finished catalyst D rich in 0.045% Os-0.15% Zr active components.

[0037] Comparative Example 5 1) 100 g of alumina, 30 g of silica and 5 g of cellulose were uniformly mixed, pressed into tablets, dried at 130 °C for 3 h, and calcined at 550 °C for 4 h to obtain a silica-alumina composite carrier; 2) 0.008 mol / L of Ru-rich active component was prepared 3+ The silicon-aluminum composite carrier is immersed in the solution for 2 hours; 3) after being taken out, it is dried at 120°C for 2 hours and calcined at 400°C for 2 hours to obtain a catalyst product E rich in 0.04% active component Ru.

[0038] Comparative Example 6 1) 102g of alumina powder and 5g of cellulose were uniformly mixed, extruded, dried at 130℃ for 3h, and calcined at 550℃ for 4h to obtain Al 2 O 3 carrier; 2) prepare 1 mol / L salt solution rich in active component cerium; 3) put the carrier into an equal volume and immerse for 2h, take out and dry at 120℃ for 5h, and calcine at 300℃ for 2h to obtain a primary catalyst precursor; 4) prepare 0.18 mol / L solution rich in active component ruthenium, then put the primary catalyst precursor into an equal volume and immerse for 2h, take out and dry at 120℃ for 5h, and calcine at 350℃ for 2h to obtain a finished catalyst F rich in 0.9%Ru-6.3%Ce active components.

[0039] Catalyst performance evaluation Catalysts I to IX and comparative examples A to F were loaded into a continuous trickle bed reactor and reduced at 220°C and 0.5 MPa hydrogen atmosphere for 1 h; the reaction temperature was 150°C, the hydrogen pressure was 3.0 MPa, and the liquid space velocity was 0.6 h -1 , H 2 The molar ratio of ester to ether was 50, and the reaction time was 100 h and 500 h, respectively, for sampling and analysis.

[0040] The evaluation results are shown in the table below. .

[0041] It can be seen from the reaction data in the table that the catalysts Ⅰ~Ⅸ prepared by this method have a reaction temperature of 150℃, a reaction pressure of 3.0 MPa, and a liquid space velocity of 0.6h -1 , H 2 Under the condition of 50 molar ratio of ester / ester, both 100h and 500h showed good DINP conversion rate and DINCH selectivity, and good stability; while comparative examples A~F showed good conversion rate and selectivity at the initial stage of the reaction, but the conversion rate and selectivity decreased to varying degrees after 500h of reaction, and the stability was poor. Therefore, the physical and chemical analysis of the used catalysts I~IX and comparative examples A~F was carried out, and the results showed that the precious metal Os in the catalyst prepared by the method of the present invention was not lost and the carrier structure was stable (the carrier structure can be referred to in the attached Figure 1), while in Comparative Examples A~F, the precious metals were lost to varying degrees and the carrier pores were seriously blocked.

Claims

1. A method for preparing an environmentally friendly plasticizer material hydrogenation catalyst from diisononyl phthalate, characterized in that A magnesium aluminum silicate dispersion is used as a base liquid, and an alkali solution and an aluminum nitrate solution are added thereto in parallel for a neutralization reaction to obtain a primary modified sodium aluminum or potassium aluminum or sodium potassium aluminum suspension. The suspension is then mixed with calcium hydroxide and modulated with dilute hydrochloric acid to form a secondary modified calcium sodium aluminum or calcium potassium aluminum or calcium sodium potassium aluminum carrier precursor, which is then filtered, dried, and calcined to form a carrier with a multi-dimensional layered structure. The carrier is impregnated in a mixed salt solution of Os and Zr by an equal volume impregnation method at low temperature to obtain a catalyst precursor, and then the finished catalyst is obtained by washing, drying, and calcining.

2. The preparation method according to claim 1, characterized in that The steps include: a. Mix aluminum magnesium silicate and water at a mass ratio of 0.2-0.4:100 to prepare an aluminum magnesium silicate dispersion; b. Prepare 0.2~0.4mol / L aluminum nitrate solution rich in metal aluminum ions; prepare 1.25~2.5mol / L alkaline precipitant; c. Add the two solutions obtained in step b to the dispersion obtained in step a in parallel under constant temperature stirring for neutralization and precipitation, and control the end point pH value to be 7.2-8.0 to obtain a primary sodium aluminum or potassium aluminum or sodium potassium aluminum suspension; d. Dissolve calcium hydroxide in water to prepare a 0.125-0.25 mol / L (calculated as metallic calcium) suspension, control the stirring speed to 150-350 rpm, slowly add the suspension obtained in step c, and simultaneously slowly add a dilute hydrochloric acid solution with a volume ratio of 1:10-1:15, control the endpoint pH value to 7.5, and prepare a secondary calcium sodium aluminum or calcium potassium aluminum or calcium sodium potassium aluminum suspension; e. Filter the suspension obtained in step d, dry it for the first time, roast it for the first time, and sieve it to obtain a 5-10 mesh carrier; f. Prepare a mixed aqueous solution of 0.008-0.016 mol / L of osmium rich in active component and 0.04-0.12 mol / L of zirconium rich in active component, control the temperature at 10-20°C, and immerse the carrier obtained in step e in the mixed aqueous solution for 1-2 hours by an equal volume impregnation method to obtain a catalyst precursor; then immerse the impregnated catalyst precursor in a 5%-8% (by mass) NaBH4 solution for 1-2 hours, take it out, wash it with distilled water, dry it for the second time, and calcine it for the second time to obtain a finished catalyst.

3. The preparation method according to claim 2, characterized in that The aluminum nitrate solution is a solution prepared by dissolving aluminum nitrate nonahydrate in water; the alkaline precipitant is a solution prepared by dissolving one or both of sodium hydroxide and potassium hydroxide in water, and the molar ratio of Na:K in a mixed solution of sodium hydroxide and potassium hydroxide is 1:

1.

4. The preparation method according to claim 2, characterized in that The constant temperature is 50~70℃ using an oil bath and the stirring speed is 100~300rpm.

5. The preparation method according to claim 2, characterized in that During parallel flow, the rate of adding aluminum nitrate solution is 15-30 ml / min, and the rate of adding alkaline precipitant is 10-20 ml / min.

6. The preparation method according to claim 2, characterized in that The mixed solution of active components osmium and zirconium is a mixture of potassium chloroosmate and zirconium nitrate.

7. The preparation method according to claim 2, characterized in that The molar ratio of Al: Ca in the carrier is 0.8~1.6:

1.

8. The preparation method according to claim 2, characterized in that The first drying temperature is 120~160℃, and the first calcination temperature is 550~650℃.

9. The preparation method according to claim 2, characterized in that The loading amounts of the active components osmium and zirconium are 0.06-0.12% and 0.15-0.45% of the catalyst weight respectively.

10. The preparation method according to claim 2, characterized in that The second drying temperature is 110~130℃, the second calcination temperature is 350~450℃, and the calcination atmosphere is nitrogen.

Citation Information

Patent Citations

  • Preparation method of catalyst applied to hydrogenation of diisononyl phthalate to synthesize diisononyl hexahydrophthalate

    CN111036279A

  • Eggshell type catalyst, preparation method and application thereof, and method for preparing cyclohexane-1, 2-dicarboxylic acid diester through selective hydrogenation

    CN115709064A

  • Catalyst and method for hydrogenating aromatic compounds

    US7361714B2

  • Catalyst for preparing alcohol by hydrogenising acetate and preparation method of catalyst

    CN103816908A

  • Catalyst supports and catalyst systems and methods

    CN116133747A